Find trusted answers to your questions with the help of IDNLearn.com's knowledgeable community. Get accurate and comprehensive answers from our network of experienced professionals.
Sagot :
Answer:
x=3 x=-2
Step-by-step explanation:
(x-3)(x+2)=0
Using the zero product property
x-3 =0 x+2 =0
x=3 x=-2
Answer:
3 and -2
Step-by-step explanation:
x -3 =0
x= 3
x+2 =0
x= -2
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Your questions find answers at IDNLearn.com. Thanks for visiting, and come back for more accurate and reliable solutions.